Optical controlled non-equilibrium processes: effect of excitation wavelength. (6th June 2019) - Bhattacharjee, Sinjini; Patra, Aniket; Pathak, Arup Kumar; Samanta, Alok Kumar
Abstract: Experimental results on optically controlled non-equilibrium solvation dynamics show their dependence on excitation wavelength, λ ex . However, the renowned Onsager regression hypothesis and Smoluchowski equation-based approach fail to explain such dependance. Failure of this theory prompted us to develop a novel theory by projecting the dynamics in a higher-dimensional space onto a one-dimensional energy gap space, where the effect of λ ex is included explicitly. We have then derived hierarchical equations of moments in time domain for an anharmonic potential based on the new kinetic equation derived here in the energy gap space to evaluate the non-equilibrium solvation time correlation function (NSTCF). The new methodlogy presented here also removes the difficulties in perturbative approaches to evaluate the NSTCF in a condensed phase. We have also shown that the NSTCF is independent of excitation wavelength for harmonic potential but dependent on the same for anharmonic potential, which is in accord with experimental observation. However, Onsager's regression hypothesis-based prediction for the NSTCF is independent of excitation wavelength for all kinds of potentials. More importantly, the calculated results of NSTCF is in excellent agreement with the experimental results where the Onsager regression hypothesis-based prediction fails.